Step 1: Begin by evaluating each term separately.
Step 2: For \( \tan^{-1}(-1) \), we know that: \[ \tan^{-1}(-1) = -\frac{\pi}{4}, \] since the tangent of \( -\frac{\pi}{4} \) is \( -1 \).
Step 3: Next, evaluate \( \sec^{-1}(-2) \). The value of \( \sec^{-1}(-2) \) corresponds to the angle \( \theta \) such that \( \sec \theta = -2 \).
Since \( \sec \theta = \frac{1}{\cos \theta} \), we have \( \cos \theta = -\frac{1}{2} \), and the angle that satisfies this condition is \( \theta = \frac{2\pi}{3} \) (since \( \cos \frac{2\pi}{3} = -\frac{1}{2} \)).
Step 4: Now, evaluate \( \sin^{-1}\left( \frac{1}{\sqrt{2}} \right) \). The angle whose sine is \( \frac{1}{\sqrt{2}} \) is \( \frac{\pi}{4} \), since \( \sin \frac{\pi}{4} = \frac{1}{\sqrt{2}} \).
Step 5: Now, add all the results together: \[ \tan^{-1}(-1) + \sec^{-1}(-2) + \sin^{-1}\left( \frac{1}{\sqrt{2}} \right) = -\frac{\pi}{4} + \frac{2\pi}{3} + \frac{\pi}{4}. \]
Step 6: Simplify the expression: \[ -\frac{\pi}{4} + \frac{\pi}{4} = 0, \] so the expression becomes: \[ \frac{2\pi}{3}. \] Thus, the final value is: \[ \tan^{-1}(-1) + \sec^{-1}(-2) + \sin^{-1}\left( \frac{1}{\sqrt{2}} \right) = \frac{2\pi}{3}. \]
If the value of \( \cos \alpha \) is \( \frac{\sqrt{3}}{2} \), then \( A + A = I \), where \[ A = \begin{bmatrix} \sin\alpha & -\cos\alpha \\ \cos\alpha & \sin\alpha \end{bmatrix}. \]